Code Mixing Used by the Teacher in Teaching English at SMP Negeri 14 Baubau - Nur Melansari; Asti Wahyuni B; Baharudin Adu; Narni Narni (FKIP, Universitas Palangka Raya, 2023)
The purpose of the study was to identify the most common types of code mixing employed by the teacher at SMP Negeri 14 Baubau, as well as the justifications for doing so. The research used a descriptive qualitative approach. One of the English teachers at SMP Negeri 14 Baubau was the subject. Interviews and observation were used as the data collection methods. Data reduction, data visualization, and conclusion drawing/data verification were the three data analysis techniques used in this study. Based on the results of this study, the teacher at SMP Negeri 14 Baubau employed insertion, alternation, and congruent lexicalization as three different methods of code mixing. The most common type of code mixing used was alternation. The results of the interview session revealed that the instructor at SMP Negeri 14 Baubau mixed codes when teaching English in the classroom because of the students' poor English proficiency and habit. It made it simpler for students to comprehend the lessons that the teacher was conveying or explaining by using code mixing when teaching English.